Etika Guru PAK bagi Sikap Etis Politik Identitas Dalam Mereduksi Superioritas - Desi Wisari; Reni Triposa; Yonatan Alex Arifianto (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2022)
This study aims to describe the ethical paradigm and the role of the Christian Religious Education teacher profession in addressing identity politics with ethical actions in an effort to reduce superiority. The ethical attitude and professionalism of Christian Religious Education teachers play an important role in educating and instilling Christian values in students. So that it can reduce the superiority in identity politics that often occurs in community groups. Identity politics occurs when minority identity groups are excluded from majority identity groups. Therefore, through this research, the author conveys that through the ethical paradigm and the teaching profession of Christian Religious Education, it will actually help efforts in reducing the superiority of identity politics. Using a descriptive qualitative method with a literature study approach, it can be concluded that the indicators of the paradigm and nature of ethics, as well as the role of the Christian Religious Education teacher presented in this study can assist the reader in understanding how the ethics and profession of Christian Religious Education teachers for the ethical attitude of identity politics in attempts to reduce superiority.